Potential applicability of virtual reality in implant dentistry: a narrative review - Alasiri, Mansour (Frontiers in Dental Medicine, 2024)
Dental implants have a high success rate but face challenges such as improper positioning, implant fracture, and tissue damage, often due to the lack of surgical proficiency. Virtual reality (VR) technology has emerged as a transformative solution in implant dentistry, offering a three-dimensional (3D), immersive environment for both educational and clinical applications. Initially used as a teaching aid, VR now facilitates comprehensive preoperative planning and precise implant placement, minimizing procedural errors. VR systems enhance student and novice surgeon training by providing a risk-free platform for skill development. Clinically, VR aids in accurate implant positioning through computer-guided surgical stents and simulation of surgical fields, improving patient outcomes by reducing complications. Furthermore, VR enhances patient education and communication, offering visual representations of treatment plans, thereby increasing patient satisfaction and understanding. Despite its benefits, VR integration faces challenges, including high costs, steep learning curves for experienced surgeons, and potential disruption of patient-clinician interactions. Developing affordable, compact VR systems and integrating VR early in dental curricula will facilitate widespread adoption and revolutionize implant dentistry by improving both surgical training and patient care. The review covers the historical development and current progress of VR with an overview of applications of VR in implant dentistry, its benefits in implant dentistry, challenges, and future perspectives.